Hyperkalemia: An archenemy in emergency medicine. Description of two case reports - Naclerio, C; Gatto, A Del; Cavallera, A (Journal of Cardiology and Cardiovascular Medicine, 2018)
Potassium is an important ion capable to maintain intra-extracellular electric gradient. Variations in the intra-extracellular ionic flow may alter cells functions, skeletal and smooth muscle contractility and electric activity of myocardial cells. In this study we demonstrated that high level of serum potassium may be associated with cardiac and neurological life-threatening diseases. We describe two case reports in which one patient, chronic hemodialysed, presented with cardiogenic shock in setting of hyperkalemia; the other, with end-stage kidney disease, showed a flaccid paralysis associated to high level of serum potassium during potassium sparing diuretic therapy. Emergency haemodialysis was performed with a complete remission of the clinical manifestations. Indeed, the use of simply diagnostic instruments such as serum electrolyte assay and electrocardiographic study (ECG) are helpful in clinical practice solving in timely serious complications due to hyperkalemia.